PENGEMBANGAN MEDIA AUDIO-VISUAL PADA MATA DIKLAT MENERAPKAN EFEK KHUSUS PADA OBJEK PRODUKSI BERBASIS PROJECT BASED LEARNING UNTUK SISWA KELAS XII SMK NEGERI 3 SINGARAJA - Ketut Satria (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This research was aimed at: (1) developing audio-visual media in a course on applying special effects to the production object based on project based learning for XII students of SMK Negeri 3 Singaraja; and (2) studying the response of the students and teachers to the development of audio-visual media in a course on applying special effects to the production object based on project based learning for XII students of SMK Negeri 3 Singaraja. The subjects of the study were 29 students in grade XI of multimedia program of SMK Negeri 3 Singaraja in the academic year 2011/2012.This research was a research and development. The data collected were the students and teacher’s responses in a course on applying special effects to the production object based on project based learning for XII students of SMK Negeri 3 Singaraja by using questionnaires. The responsed data of students and teachers were analyzed descriptively. The results of this study show that students responses to the development of audiovisual media in a course on applying special effects to the production object based on project based learning for XII students of SMK Negeri 3 Singaraja was very positive on the category of 0%, positive 86.21%, 13.79% uncertain, negative 0 % and 0% very negative. The average score was 52.86. While the average score for teacher’s responses was 51. Thus, the students and teacher’s responses was categorized as positive.